Complement C3 of tumor-derived extracellular vesicles promotes metastasis of RCC via recruitment of immunosuppressive myeloid cells - Yibi Zhang; Xiaodong Wang; Yinmin Gu; Tongfeng Liu; Xujie Zhao; Shuwen Cheng; Liqiang Duan; Chang Huang; Songzhe Wu; Shan Gao (Proceedings of the National Academy of Sciences, 2025)
Heterogeneous roles of complement C3 have been implicated in tumor metastasis and are highly context dependent. However, the underlying mechanisms linking C3 to tumor metastasis remain elusive in renal cell carcinoma (RCC). Here, we demonstrate that C3 of RCC cell-derived extracellular vesicles (EVs) contributes to metastasis via polarizing tumor-associated macrophages (TAMs) into the immunosuppressive phenotype and recruiting polymorphonuclear myeloid-derived suppressor cells (PMN-MDSCs). Mechanistically, EV C3 induces the secretion of CCL2 and CXCL1 by lung macrophages and subsequently enhances TAM polarization and PMN-MDSC recruitment. Notably, targeting the CCL2/CCR2 or CXCL1/CXCR2 axis with the inhibitors RS504393 or Navarixin, respectively, effectively suppresses lung metastasis induced by RCC-derived C3 in a mouse model. Clinically, RCC patients with high expression of C3 demonstrate poor prognosis. Collectively, our findings reveal that tumor-derived EV C3 induces an immunosuppressive tumor microenvironment via TAMs, and thus promoting RCC metastasis.